Enhancing energy management in IoT networks - Mota, J.; Coutinho, C. (Procedia Computer Science, 2025)
The Internet of Things is nowadays available everywhere, collecting data that can be used for different purposes. These end-devices are available in different formats, and depending on the use case, they need different features in order to function properly. Due to their specific requirements, some of these devices need to be portable, so a battery is an important component. Additionally, choosing the right communication protocol for these particular use cases is essential for establishing a network connection while minimising energy consumption. This will ensure that the collected data is transmitted for further analysis. This paper aims to provide an overview of LoRa, LoRaWAN, and Duty Cycling, along with their advantages and disadvantages in terms of energy efficiency on Internet of Things devices. Lastly, a suggested architectural design is proposed based on an energy-efficiency strategy, and some scenarios are assessed and compared in order to determine which could be preferred when it comes to an energy efficient solution.